2015
DOI: 10.1051/swsc/2015016
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint observation of the response of the magnetosphere and ionosphere related to the sudden impulse event on 19 November 2007

Abstract: The aim of this study is to provide a complete scope of a magnetic sudden impulse (SI) event along its way through interplanetary space and the magnetosphere until its arrival to the ground. In our case, we chose the event of 19th November 2007 because of the availability of enough well-located spacecraft at that moment for our purpose. We have used a 16 spacecraft data set. We calculated the mass flux variation and the change in magnetic field components across the discontinuity. Thus, we identified the solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…An additional constraint of the identification of the sudden commencement is that it happens quasi-simultaneously (<1 min) at all latitudes (e.g. Engebretson et al, 1999;Segarra et al, 2015). In our study we have used magnetometer stations at Abisko (ABK, 68 • N), Lerwick (LER, 60 • N), Fürstenfeldbruck (FUR, 48 • N), Bangui (BNG, 4 • N), Ascension Island (ASC, 8 • S), and Mawson (MAW, 67 • S) which are part of the INTERMAGNET consortium (Love and Chulliat, 2013).…”
Section: Delay Measurement and Databasementioning
confidence: 99%
“…An additional constraint of the identification of the sudden commencement is that it happens quasi-simultaneously (<1 min) at all latitudes (e.g. Engebretson et al, 1999;Segarra et al, 2015). In our study we have used magnetometer stations at Abisko (ABK, 68 • N), Lerwick (LER, 60 • N), Fürstenfeldbruck (FUR, 48 • N), Bangui (BNG, 4 • N), Ascension Island (ASC, 8 • S), and Mawson (MAW, 67 • S) which are part of the INTERMAGNET consortium (Love and Chulliat, 2013).…”
Section: Delay Measurement and Databasementioning
confidence: 99%
“…From the vast number of solar windmagnetosphere studies the commonly used parameters for predictions are solar wind magnetic field component B z , or both B y and B z , particle density n, and speed V, or expressed as the dynamic pressure p ∝ nV 2 and the convective electric field component E y ≈ ÀVB z . The dynamic pressure plays an important role in the creation of the global geomagnetic disturbances known as sudden impulses (SI) (Segarra et al, 2015), which becomes classified as a SSC if there is a subsequent storm, while the solar wind electric field E y is generally considered to control the reconnection rate (Pulkkinen et al, 2007), although it has been suggested that it is not the solar wind electric field that controls the reconnection rate but it works due to a coincidence (Borovsky and Birn, 2014). As the neural network can approximate continuous functions arbitrarily well (Cybenko, 1989) the individual solar wind parameters can be provided as inputs from which the relations are found.…”
Section: Algorithmsmentioning
confidence: 99%
“…The interaction of a shock with the magnetosphere could have global effects, leading to magnetic/electric field and plasma perturbations in the magnetosphere and ionosphere. Sudden magnetic field changes have been investigated using multisatellite observations and numerical MHD simulations [e.g., Samsonov et al, 2014;Segarra et al, 2015]; transient electric field has also been observed in the dayside magnetosphere which was directed westward [Shinbori et al, 2004]. In accordance, plasma motion has been reported to be earthward around the geosynchronous orbit, based on in situ observations of 1.2 keV electron [Baumjohann et al, 1983] and ions with energies from a few eV/e to tens of keV/e [Keika et al, 2008;Zhang et al, 2012].…”
Section: Introductionmentioning
confidence: 99%